2002
DOI: 10.1021/jp0265081
|View full text |Cite
|
Sign up to set email alerts
|

The Silver Chloride Photoanode in Photoelectrochemical Water Splitting

Abstract: Thin silver chloride layers evolve oxygen under UV/vis illumination in aqueous solution under appropriate conditions. AgCl deposited on a conducting support photocatalyzes the oxidation of water to O2 in the presence of a small excess of silver ions in solution. The light sensitivity in the visible part of the spectrum is due to self-sensitization caused by reduced silver species. Anodic polarization reoxidizes the reduced silver species. Considerable improvement of sensitivity has been observed with AgBr sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
61
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 96 publications
(65 citation statements)
references
References 30 publications
4
61
0
Order By: Relevance
“…It has been shown that a thin silver chloride layer deposited on a conducting support photocatalyzes the oxidation of water to O 2 in the presence of an excess of silver ions [73]. Silver cations adsorbed at the surface of silver chloride nanocrystals are necessary for the reaction to proceed.…”
Section: Photocatalytic and Photoelectrochemical Water Splittingmentioning
confidence: 99%
“…It has been shown that a thin silver chloride layer deposited on a conducting support photocatalyzes the oxidation of water to O 2 in the presence of an excess of silver ions [73]. Silver cations adsorbed at the surface of silver chloride nanocrystals are necessary for the reaction to proceed.…”
Section: Photocatalytic and Photoelectrochemical Water Splittingmentioning
confidence: 99%
“…The internalization of nano-AgX into polymeric matrix offers the composite extensive industrial viabilities that combine features of organic and inorganic materials [11][12] . They provide composite materials having antimicrobial, optical and electrical applications 10 , catalyst and photochromic materials [13][14] .…”
Section: Introductionmentioning
confidence: 99%
“…1,2 It also has photocatalytic activities that are useful for water splitting and decomposition of organic pollutants. [3][4][5][6] It has been demonstrated that decoration of AgCl with Ag nanoparticles can greatly improve the light absorption property and photostability of the AgCl nanoparticles. [7][8][9] In addition, AgCl can be used in fabricating antiseptic catheters, bone cements, and fabrics owing to its antibacterial property.…”
Section: Introductionmentioning
confidence: 99%